Q: What is 6x-2 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x2

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

One-houndred and thirty five.

-6x2 + 3x - 4 can be factored into (-x + 4)(x + 1). This equals 0 only when x is either 4 or -1. Therefore, the latter two numbers are both roots of the given function.

It has two solutions and they are: x = 3.230396696 and x = -2.063730029

Related questions

6x2

10x2 - 56 = 88 - 6x2 : 10x2 + 6x2 = 88 + 56 : 16x2 = 144 : x2 = 9 : x = ± 3

10x2 - 64 = 36 + 6x2; whence, 4x2 - 100 = 0, x2 = 25, and x = ±5.

6x2+13x-5 = 0 (2x+5)(3x-1) = 0 x = -5/2 or x = 1/3

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

No. 6 x 2 = 2 x 6 is.

One-houndred and thirty five.

-6x2 + 3x - 4 can be factored into (-x + 4)(x + 1). This equals 0 only when x is either 4 or -1. Therefore, the latter two numbers are both roots of the given function.

Im assuming the "6x2" is supposed to be 6x squared. The factored form would be (2x+1) (3x-8)

x = -1/3 or 11/2 3 = 6x2 - 7x ⇒ 6x2 - 7x - 3 = 0 ⇒ (3x + 1)(2x - 3) = 0 ⇒ (3x + 1) = 0 → x = -1/3 or (2x - 3) = 0 → x = 11/2

It is: 12-4(6*-1) = 25

If that's 6x2, the answer is (2x + 1)(3x - 2)